New and poorly known species of Neonesidea (Bairdiidae, Ostracoda, Crustacea) from French Frigate Shoals, the Hawaiian Islands - Maddocks, Rosalie F. (Zootaxa, 2013)
Neonesidea tenera and four new species (N. plumulosa, N. holdeni, N. bacata, N. edentulata) are described from scrapings of spur and groove habitats on French Frigate Shoals and O’ahu, Hawaiian Islands. Some anatomical details have potential taxonomic significance for the genus Neonesidea, including the caudal setae of the carapace, the masticatory apparatus, and the antennal claw.